The Effectiveness of Wearable Devices as Physical Activity Interventions for Preventing and Treating Obesity in Children and Adolescents: Systematic Review and Meta-analysis - Wentao Wang; Jing Cheng; Weijun Song; Yi Shen (JMIR Publications, 2022)
BackgroundThe prevalence of obesity in children and adolescents remains a global public health issue. Wearable devices may offer new opportunities for prevention and intervention in obesity. Previous systematic reviews have only examined the effect of the wearable device interventions on preventing and treating obesity in adults. However, no systematic review has provided an evaluation of wearable devices as physical activity interventions for preventing and treating obesity in children and adolescents. ObjectiveThe purpose of this review and meta-analysis was to evaluate the effectiveness of wearable devices as physical activity interventions on obesity-related anthropometric outcomes in children and adolescents. MethodsResearch articles retrieved from PubMed, EMBASE, Cochrane Library, Scopus, and EBSCO from inception to February 1, 2021, were reviewed. The search was designed to identify studies utilizing wearable devices for preventing and treating obesity in children and adolescents. The included studies were evaluated for risk of bias following the Cochrane recommendation. Meta-analyses were conducted to evaluate the effectiveness of wearable devices as physical activity interventions on body weight, body fat, BMI z-score (BMI-Z), BMI, and waist circumference. Subgroup analyses were performed to determine whether the characteristics of the interventions had an impact on the effect size. ResultsA total of 12 randomized controlled trials (3227 participants) were selected for meta-analysis. Compared with the control group, wearable device interventions had statistically significant beneficial effects on BMI (mean difference [MD] -0.23; 95% CI -0.43 to -0.03; P=.03; I2=2%), BMI-Z (MD -0.07; 95% CI -0.13 to -0.01; P=.01; I2=81%), body weight (MD -1.08; 95% CI -2.16 to -0.00; P=.05; I2=58%), and body fat (MD -0.72; 95% CI -1.19 to -0.25; P=.003; I2=5%). However, no statistically significant effect was found on waist circumference (MD 0.55; 95% CI -0.21 to 1.32; P=.16; I2=0%). The subgroup analysis showed that for participants with overweight or obesity (MD -0.75; 95% CI -1.18 to -0.31; P<.01; I2=0%), in the short-term (MD -0.62; 95% CI -1.03 to -0.21; P<.01; I2=0%), wearable-based interventions (MD -0.56; 95% CI -0.95 to -0.18; P<.01; I2=0%) generally resulted in greater intervention effect size on BMI. ConclusionsEvidence from this meta-analysis shows that wearable devices as physical activity interventions may be useful for preventing and treating obesity in children and adolescents. Future research is needed to identify the most effective physical activity indicators of wearable devices to prevent and treat obesity in children and adolescents.